Agribisnis Perkebunan di Kabupaten Cilacap Provinis Jawa Tengah - Agus Dwi Nugroho; Mais Ilsan; Efrinda Efrinda; Winaryo Winaryo; Rini Handoyo; Suparmono Suparmono; Reineta Puspitasari (Politeknik Negeri Lampung., 2017)
Plantation is considered strategic in Cilacap, but now the condition of farmers are marginalized. Therefore, it is necessary to do research to find out the main plantation crops in Cilacap and the strategy to development. This research was conducted in June-August 2016. The data used is primary data through observations, interviews farmer and agricultural bureau. The secondary data collected from the relevant agencies. Analysis of data using Location Quotient, Rasmussen's Dual Criterion and SWOT. The main commodities for plantation crops are coconut, rubber and nutmeg. In order to develop agribusiness need improving the human resources quality; increasing promotional and information efforts of main commodities for investors; extending the land, controlling over land use, guaranting prices of commodities, climate change mitigation, infrastructure development and credit accessibility for farmers.